Освіта в Україні під час нацистської окупації (на матеріалах Дніпропетровської області) - Беллецца, С.А. (Український історичний журнал, 2010)
У статті проаналізовано ситуацію у сфері освіти в ґенеральній окрузі Дніпропетровськ із точки зору діалектики наказів німецьких керівників та заходів, що їх уживали місцеві допоміжні адміністративні структури. Показано, як в освітній галузі втілювались основні риси національної (расової) та соціальної політики окупантів. Mainly using the documents of collaborative administration, this article analyses the school policy of the Generalbezirk Dnjepropetrowsk during Nazi occupation of Ukraine. Differently from other regions, in Dnipropetrovs’k schools and even universities were allowed to re-open, thanks to the positive attitudes of the local Commissar, Claus Selzner, who was a supporter of Alfred Rosenberg’s faction within the Nazi Party. A key figure of this system was the historian Pavlo Kozar, a victim of Stalinist repressions, later dismissed by the Nazi’s because of his strongly national views. After the fall 1942, all universities and many schools were closed, following the more repressive politics of General Commissar Erich Koch, thus irremediably intimidating younger generations, who saw the Soviet educational system as a way of social promotion.